Nowe stanowiska, rozmieszczenie i ochrona buławnika czerwonego Cephalanthera rubra (L.) Rich. (Orchidaceae) w Puszczy Augustowskiej (NE Polska) - Lewoń, Radosław; Romański, Maciej (Leśne Prace Badawcze, 2024)
Cephalanthera rubra (L.) Rich. is a strictly protected species in Poland, which is very rare in the northeastern part of the country (Suwałki region). In recent years, two sites were discovered in the Wigry National Park. We present a description of the new sites and distribution of the red helleborine in the Augustów Forest, NE Poland.